KETIDAKEFEKTIFAN KALIMAT DALAM SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Sholihin Sholihin; Mangatur Sinaga; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This study titled as ineffectiveness of sentence in thesis of bahasa indonesia literature and education sciene of riau university students. This study aims to determine the effectiveness of the sentence and explain the causes of the ineffectiveness of the sentence student thesis PSPBSI in 2014. Using descriptive analysis method with qualitative approach. PSPBSI student theses as year of 2014 that amounted to 57 theses are the data of this study. The result found (1) 80 sentences are not effective caused by not having the element of unity, (2) 21 sentences are not effective caused by not having the equivalent element, (3) 52 sentences are not effective caused by not having the element of effectiveness, (4) 49 sentences are not effective caued by dictional imprecision, (5) 32 ineffectivenes caused by not having the logic element, (6) 51 ineffective sentences caused by not having singleness of meaning element.Keywords: ineffectiveness of sentence, in thesis, of bahasa indonesia literature and education sciene, of riau university students